THEORITICAL ANALYSIING THE PROBLEM IN KORRESPONDING OF TOURISM TEXTS - Isroiljon kizi, Gavharoy (Innovative Development in Educational Activities, 2023)
This paper focuses on one particular parallel development in linguistics and translation studies, namely terms of the business tourism analysis of language use. Recent years have seen the compilation of translations, designed specifically to investigate the language and features of translation, usually by comparing translations with non-translations.